For Sake of The Economic Reform - With some indication for Iraq - عبد الحميد علاء (Journal of Economics and Administrative Sciences, 2018)
The imbalances and economic problems which it face the countries, it is a result of international economic developments or changes or global crises such as deterioration in trade, sharp changes in oil prices, increasing global indebtedness, sharp changes in foreign exchange rates and other changes, all that, they affect the economic features of any country. and These influences vary from one country to another according to the rigidity of its economy and its potential in maneuvering with economic plans and actions that would reduce the impact or avoidance with minimal damage. Therefore, the countries that suffer from accumulated economic problems as a result of mismanagement and poor planning or suffer from the lack of economic resources and scarcity, It will be more vulnerable to these influences and must make decisions and economic plans to promote their economies. and They must resort to working for economic reforms and announce a program of action for those reforms that would help them overcome their crises. In this paper, we will discuss the concept of economic reform and the purpose of its implementation and the role of the State and its appropriate procedures for its implementation. In the second section, we will discuss some of the laws and laws that should be encouraging to support economic reform, also discussed the priority to the implementation of reforms and social justice in practice, On the third section, the experiences of the economic reform of certain countries, such as China, Turkey and the UAE, and its development under the reform measures, were briefly discussed.